1996
DOI: 10.7589/0090-3558-32.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ivermectin Against Nematodes Infecting Field Populations of Snowshoe Hares (Lepus Americanus) in Yukon, Canada

Abstract: From July 1990 to February 1991, nematode numbers in free-ranging snowshoe hares (Lepus americanus) at Kluane Lake, southwestern Yukon, Canada, were manipulated by subcutaneous injection (0.4 mg/kg) of ivermectin. Three field experiments were conducted to determine the degree of helminth loss associated with a single administration of ivermectin; the length of time that ivermectin was effective in reducing worm numbers; and the effect of repeated ivermectin administration in reducing worm numbers. Numbers of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…There may be differences in the activity of the anthelmintics against adult strongyles and immature larvae, especially those inhibited within the tissues, although the propensity for macropodid nematodes to undergo hypobiosis has not been studied. In the case of injectable anthelmintics such as ivermectin and moxidectin, Sovell and Holmes (1996) suggested that infrequent local tissue reactions at the site of injection can restrict drug action and limit the amount of drug delivered into the blood stream, but it was not possible to assess this in our field study.…”
Section: Discussionmentioning
confidence: 41%
“…There may be differences in the activity of the anthelmintics against adult strongyles and immature larvae, especially those inhibited within the tissues, although the propensity for macropodid nematodes to undergo hypobiosis has not been studied. In the case of injectable anthelmintics such as ivermectin and moxidectin, Sovell and Holmes (1996) suggested that infrequent local tissue reactions at the site of injection can restrict drug action and limit the amount of drug delivered into the blood stream, but it was not possible to assess this in our field study.…”
Section: Discussionmentioning
confidence: 41%
“…In regard to the need for an efficient antiparasitic control for onchocerciasis, moxidectin is currently under development in man (Cotreau et al 2003). In the rabbit, MLs are effective against ectoparasites (psoriatic mange; Wright and Riner 1985;Wagner and Wendlberger 2000) and nematodes (Sovell and Holmes 1996). Although there is no specific formulation available for rabbits, moxidectin represents a good alternative for broad-spectrum antiparasitic therapy in this species.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no specific formulation available for rabbits, ivermectin represents a good drug for broad-spectrum antiparasitic therapy in this species. Indeed, MLs are effective against ectoparasite, psoriatic mange (Wagner and Wendlberger 2000;Wright and Riner 1985), and nematodes (Sovell and Holmes 1996).…”
Section: Introductionmentioning
confidence: 99%